Reforestation of Cunninghamia lanceolata changes the relative abundances of important prokaryotic families in soil - Hou, Xue-Yan; Qiao, Wen-Tao; Gu, Ji-Dong; Liu, Chao-Ying; Hussain, Muhammad Mahroz; Du, Dao-Lin; Zhou, Yi; Wang, Yong-Feng; Li, Qian (Frontiers in Microbiology, 2024)
Over the past decades, many forests have been converted to monoculture plantations, which might affect the soil microbial communities that are responsible for governing the soil biogeochemical processes. Understanding how reforestation efforts alter soil prokaryotic microbial communities will therefore inform forest management. In this study, the prokaryotic communities were comparatively investigated in a secondary Chinese fir forest (original) and a reforested Chinese fir plantation (reforested from a secondary Chinese fir forest) in Southern China. The results showed that reforestation changed the structure of the prokaryotic community: the relative abundances of important prokaryotic families in soil.This might be caused by the altered soil pH and organic matter content after reforestation. Soil profile layer depth was an important factor as the upper layers had a higher diversity of prokaryotes than the lower ones (p < 0.05). The composition of the prokaryotic community presented a seasonality characteristic. In addition, the results showed that the dominant phylum was Acidobacteria (58.86%) with Koribacteraceae (15.38%) as the dominant family in the secondary Chinese fir forest and the reforested plantation. Furthermore, soil organic matter, total N, hydrolyzable N, and NH 4 + -N were positively correlated with prokaryotic diversity (p < 0.05). Also, organic matter and NO 3 --N were positively correlated to prokaryotic abundance (p < 0.05). This study demonstrated that re-forest transformation altered soil properties, which lead to the changes in microbial composition. The changes in microbial community might in turn influence biogeochemical processes and the environmental variables. The study could contribute to forest management and policymaking.